EFEKTIVITAS PENGEMBANGAN MEDIA POP-UP BOOK BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Dede Maria Ulfah; Yoyo Zakaria Ansori; Ani Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the characteristics of development and the effectiveness of local wisdom-based Pop-Up Book media in improving elementary school students’ learning outcomes through a Systematic Literature Review (SLR) using the PRISMA approach. The data were obtained from 14 selected articles that were systematically analyzed based on predefined inclusion criteria. The results indicate that the majority of studies employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed media consistently integrates local wisdom as a contextual learning approach. In terms of effectiveness, Pop-Up Book media has been proven to improve students’ learning outcomes, as indicated by N-Gain scores ranging from moderate to high categories and a significant effect on learning motivation. In addition, the media is considered valid and practical for classroom implementation. Therefore, local wisdom-based Pop-Up Book media is effective in enhancing elementary school students’ learning outcomes.